Aplicaciones tecnológicas de la envasadora de fluidos de baja densidad en procesos de transformación agroindustrial - Crespo Martínez, Alex Javier (2024)
The laboratories of the Agroindustry career are extremely important to teaching pedagogical practices where students can acquire knowledge about each topic to be carried out in the different types of machinery located within the laboratories. The project aimed to carry out technological applications of the low-density fluid packaging machine in agro-industrial transformation processes. For which the machinery was characterized to know its operation. The preparation of operating and maintenance manuals is essential for the management of said machinery and being able to establish the best way to keep it in good condition without affecting any product used in the use of the machinery, which can be checked the use of the manuals on different types of practices such as the preparation of nectars, juices, yogurt which must be properly packaged in the low-density fluid packaging machine. The low-density fluid packaging machine in the developed practices performed very well in the different products, thus being able to be applied in different industries, such as fruit and dairy drinks, taking into account that it can only package liquids that do not have fruit pieces or fibers, which may obstruct the filters from functioning. In the practices developed in agribusiness laboratories, it was applied in these different areas, being of great help in the packaging of juices, nectars, and dairy drinks (yogurt), each drink had a different calibration, it must be taken into account when packaging, due to the different viscosities that these products have.